Judicial Independence in Japan: A Re-Investigation for China - Lin, Laifan (Columbia Journal of Asian Law, 1999)
In their discussions concerning judicial independence, many jurists have formulated far-reaching and complex versions of legal culture. From a comparative approach, in the political-legal tradition of many European countries, the notion of state judicial power involved in the settlement of criminal cases and even civilian disputes as a neutral party is quite acceptable. However, as will be discussed, in the history of Asian countries such as China and Japan, judicial power and administrative power have long been one integrated mass, and thus, it is difficult to establish an independent image of judicial power, which may be the situation in China today. The principle of judicial independence that originated in the West was put into effect with the establishment of the modem idea of “separation of powers.” Nonetheless, countries such as China and Japan face a long and winding process to establish judicial independence in their countries. If legal cultures are inevitably linked, phenomena in the abovementioned legal culture will indeed corroborate a regular pattern of development of legal culture. However, this concept must surmount the notion of a kind of determinism. Since the early 19th century, with the impact of western legal culture, Asian countries such as Japan and China have gradually realized that judicial independence is not only a premise of “fair jurisdiction,” but also a basic condition indispensable for the establishment and development of the rule of law. These countries have self-consciously started to absorb the concept and principles of judicial independence and made various attempts to establish relevant systems. While China and Japan are both “eastern” countries, they have experienced quite different outcomes due to the differences in the two societies and their respective historical conditions. Japan has basically accomplished the historical task of setting up the foundations for judicial independence. On the other hand, China still suffers various obstacles in the process of accomplishing this historical task, and faces various problems.